Kajian Awal Penerapan Reverse Engineering pada Desain Brace Kifosis - Finny Pratama Putera; Paryana Puspaputra; Muhammad Arkan Hidayat (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
Kyphosis is a physical disorder that occurs in the human spine. This symptom is characterized by an abnormal curvature of the spine. For this reason, one of the healing therapies is needed, namely a kyphosis brace. This brace is designed and made by applying the reverse engineering method. The design begins with a scanning process using a 3D scanner. Then continued with the process of redrawing the body shape with reference to the image from the 3D scanner results. This redrawing process uses Autodesk Fusion software with various features including modify edit form, modify subdivide, modify merge edge, and symmetry. A kyphosis brace design is produced that can be continued to be produced to the next stage by 3D Printer.